Design, Synthesis and Evaluation of Thioacetamide-Tethered Thiadiazole-1,2,4-Triazole Hybrids as SHP2 Inhibitors for Cancer Therapy - Mitra R.; Kumar S.; Chaudhuri A.; Agrawal A.K.; Ayyannan S.R. (My University, 2025)
Src homology-2 (SH2) domain-containing phosphatase-2 (SHP2), the first protooncogenic phosphatase is a key mediator in the development and progression of various cancers. Several allosteric sites have been identified in SHP2, inhibitors of which are being developed. In the current study, we have designed and synthesized a library of 21 thioacetamide-tethered thiadiazole-1,2,4-triazole hybrids (compounds 16–36) and evaluated their in vitro SHP2 inhibitory potential. Compound 28 (N-(5-(benzo[d][1,3]dioxol-5-yl)-1,3,4-thiadiazol-2-yl)-2-((5-(4-methoxyphenyl)-4H-1,2,4-triazol-3-yl)thio)acetamide) emerged as the most potent SHP2 inhibitor (IC50=0.318±0.001 μM) inhibiting the enzyme in a mixed to non-competitive manner. In silico studies revealed that the lead inhibitor strongly binds to the tunnel allosteric site of SHP2. Further, cytotoxicity studies revealed that compound 28 caused death of SHP2-driven MCF-7 (GI50=37.02±0.25 μM) and U87MG cells (GI50=68.69±0.21 μM) in a dose-dependent manner and inhibited MCF-7 cell colony formation and migration. Flow cytometric analysis showed that it exerted its antiproliferative effect on U87MG cells by inducing early apoptosis (Q2 phase) and inhibiting cell cycle progression at the G1 and S phase. Compound 28 was shown to increase oxidative stress in the U87 cells by promoting ROS generation and loss of mitochondrial integrity. In summary, the present study produced a potent SHP2 inhibitor (compound 28) with a promising in vitro cytotoxicity profile, thus meriting further investigation. © 2024 Wiley-VCH GmbH.